2005
DOI: 10.3168/jds.s0022-0302(05)72779-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Fatness and Glucogenic Supplement on Lipid and Protein Mobilization and Plasma Leptin in Dairy Cows

Abstract: Twenty-four multiparous Ayrshire cows were used in an experiment to test the effect of body fatness and glucogenic supplement, fed during the transition period, on lipid and protein mobilization and plasma hormone concentrations. Eight weeks before their expected calving date, the cows were divided into blocks of 4. Two cows with the highest body condition score within each block were then allocated to a test (T) group and the other 2 cows to a control (C) group. To scale up the differences between fatter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
90
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 33 publications
26
90
5
Order By: Relevance
“…The higher plasma NEFA and BHBA concentrations for cows in the high group around parturition are in accordance with other studies (Kokkonen et al, 2005;Ohgi et al, 2005;Hammon et al, 2009) and can be explained by high fat mobilization, resulting in excessive hepatic fat accumulation after calving.…”
Section: Associations Between Liver Fat Concentrations and Metabolitesupporting
confidence: 77%
See 2 more Smart Citations
“…The higher plasma NEFA and BHBA concentrations for cows in the high group around parturition are in accordance with other studies (Kokkonen et al, 2005;Ohgi et al, 2005;Hammon et al, 2009) and can be explained by high fat mobilization, resulting in excessive hepatic fat accumulation after calving.…”
Section: Associations Between Liver Fat Concentrations and Metabolitesupporting
confidence: 77%
“…On the other hand, cows in the low group, with the lowest mobilization, had the lowest plasma leptin concentrations, and cows in the high group, with highest the mobilization, had comparable plasma leptin concentrations before calving as those in the medium group but showed the greatest decrease in plasma leptin after calving. Findings by Kokkonen et al (2005) that BCS is related to plasma leptin cannot be completely confirmed by our study, but our results are in accordance with those of Hammon et al (2009). For cows in the high group, the capacity for hepatic fat oxidation was obviously limited.…”
Section: Associations Between Liver Fat Concentrations and Metabolitesupporting
confidence: 75%
See 1 more Smart Citation
“…High-yielding dairy cows are not able to compensate completely for the energy lost due to milk production during early lactation by a sufficient increase of feed intake (Bell and Bauman, 1997;Drackley et al, 2001;Kokkonen et al, 2005). This leads to the mobilization of body reserves resulting in a negative energy balance that may be associated to health problems.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid such metabolic disorders, additional energy sources like glycogen precursors (Kokkonen et al, 2005) and/or different rumen-protected fat supplements at various degrees of saturation, such as calcium soaps (Jenkins and Palmquist, 1984;Grummer, 1988), hydrogenated fatty acids (Jenkins and Palmquist, 1984) and triglycerides (Grummer, 1988) are added to the diet of highyielding or multiparous dairy cows. However, the effects of these different fat supplementations on hepatic lipid metabolism in ruminants are not fully understood.…”
mentioning
confidence: 99%